Hidup Bersama dengan Rukun untuk Membarui dalam Mazmur 133:1 (Menguatkan Penatalayanan Gereja dengan Kebersamaan dan Kerukunan Menuju Gereja yang Unggul Melayani) - Sukanto Limbong (Bulletin of Community Engagement, 2024)
The Covid-19 pandemic has had a significant impact on church life and ministry to congregants, as outlined in the paper from the XXI GKPA Synod. This research aims to analyze the changes in conventional church growth indicators, such as attendance, building utilization, and finances, which are no longer effective benchmarks in these challenging times. Utilizing a qualitative approach and case study design, this study collects data through in-depth interviews, literature reviews, and participatory observations. The findings indicate that churches are required to adapt to the era of the Fourth Industrial Revolution while emphasizing the values of harmony highlighted in Psalm 133. Churches are called to "Excel in Serving" by prioritizing solidarity and attention to vulnerable groups. Additionally, the use of technology has become essential for maintaining connections among congregants and fostering creativity in fulfilling the church's mission. In conclusion, this research underscores that the church is called to live together in harmony amidst the challenges of the pandemic and changing times. The focus of ministry is directed towards efforts that bring blessings and life to all, particularly for those who are most vulnerable, while continuously renewing practices relevant to contemporary contexts. This study aims to provide insights for churches in responding to current and future challenges.